Shock waves in real gases with different specific heat ratios ahead of and behind shock fronts - Tarnavsky, G.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2002)
A physicomathematical model of shock waves in real gases with different specific heat ratios ahead of and behind shock fronts is considered in the approximation of an infinitely thin discontinuity. Several jump relations for gas- and thermodynamic parameters are obtained; when the specific heat ratios are constant, these relations become the well-known classical relations of gas dynamics. The model applicability limits in the domain of basic parameter space are determined. Some numerical results obtained on the basis of the method we propose are given; the characteristics and peculiarities of numerical solutions are compared with those of known solutions.